Famosos que leem: uma análise discursiva de enunciações orgulhosas ou envergonhadas acerca da leitura - Fernandes, Suélen Maira Xavier (Universidade Federal de São Carlos, 2021)
This undergraduate thesis, a work of course conclusion, inserted in the research project conducted by Profa. Dr. Luzmara Curcino, entitled “Proud readers, shamed readers: emotions in discourses about reading”, aims to raise and constitute a very specific corpus of statements about reading, obtained from interviews with famous people and published in national newspapers and magazines from different segments, available on the internet. We search in which there some mention, motivated (when, due to a question, they were asked to talk about themselves), or spontaneous (when even without being asked about it, they issued comments) about the reading or about themselves as readers. More specifically, we selected statements in which was expressed some emotions in relation to reading and the reading condition, like 'pride', 'shame' and, eventually, 'nostalgia'. In this work we constitute a concise and specific corpus of statements in which these emotions about reading were expressed in interviews given by nationally known personalities from the cultural field. Supported by some principles of Discourse Analysis and Cultural History of Reading, we observe how, in terms of reading, certain statements can be polemically received, require retraction, and became a reason for the 'shame' by their enunciators, or, on the other hand, became a sufficient reason for the display of 'pride' of being a reader.
Famous people who read: a discursive analysis of proud or shamed statements about reading
Keywords: Discursos sobre a Leitura; Vergonha; Orgulho; Famosos; Entrevistas; Discourses about Reading; Shame; Pride; Famous; Interviews; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA